First-Order Regionalization of Landslide Characteristics in the Canadian Cordillera - Eisbacher, G. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1979)
Abstract Landslide modes in the Canadian Cordillera are regionalized into eight zones according to the dominance of specific types of failure and mass transport. The Coast-Insular Zone is dominated by rock falls, rock avalanches, debris and earth flows; the St. Elias Zone by rock slumps and debris flows; the Plateau Zone by earth flows and rock slumps; the Skeena Zone by rock slumps; the Yukon-Selwyn Basin Zone by rock slumps; the Cassiar-Columbia Zone by deep-seated slope-sagging and gravitational spreading; the Eastern Carbonate Zone by rock avalanches and debris flows; the Foothills Zone by soft-rock slumps and earth flows. Landslide abundance in the Canadian Cordillera is related to the complex interaction of local geology on the one hand and regional factors such as relief, intensity of precipitation, and seismicity on the other. The landslide hazard deserves special attention in the recreational hinterland of Vancouver and Calgary.